The Influence of E-Learning and Learning Interests on Learning Outcomes of Physical Education in 11th Students of SMA Negeri 8 Medan - Denny Syahputra Panjaitan; Nurhayati Simatupang; Sanusi Hasibuan; Indrakasih Indrakasih (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The purpose of this study was to explain the effect of differences in learning outcomes of physical education through edmodo and google classroom on Class XI students of SMA Negeri 8 Medan. This research method uses an experimental method with a 2x2 level design. The data analysis technique used analysis of variance. The research instrument used a questionnaire. The results of the research that have been carried out state that: (1) Based on the results of the analysis of variance in the list of attachments at the level of α = 0.05, it is obtained that F0 <Ft is 0.279 <4.11. (2) Then in the Tukey test in groups A1B1 and A2B1 where = 1.681 and = 2.95. Research conclusions: 1) There are differences in physical education learning outcomes through edmodo and google classroom.